PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP PELAKSANAAN IBADAH SHOLAT SISWA - Cantik Aisyah Nurillahi (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2020)
Prayer is an obligation for all Muslims who are puberty and having common sense. Islamic Education Learning carried out in schools is expected to increase the prayer of students. The purpose of this study was to determine the effect of Islamic Education Learning on the worship of students in Eighth Grade of SMPN Cisarua 1. This study uses quantitative methods of collegational type. Collecting data in the form of a questionnaire given to 54 respondents who are Eighth Grade students of SMPN Cisarua 1. The analysis of this research data used a collegial test with the help of the IBM SPSS version 25 program. The results of this study obtained a correlation coefficient of 0.470 which was in the range 0, 40-0.70, which means that there is a relationship between Islamic Education Learning with prayer of Eighth Grade students at SMPN Cisarua 1.